2014
DOI: 10.1002/tee.21978
|View full text |Cite
|
Sign up to set email alerts
|

Microporous activated carbons from used coffee grounds for application to electric double-layer capacitors

Abstract: Electrochemical double-layer capacitors (EDLCs) are devices that store enormous amounts of charge electrostatically when a potential is applied between electrodes of very high surface area (typically made of porous carbon) and an electrolyte. Wider commercialization of this technology has been held back by the lack of ultralow-cost electrode materials. We demonstrate that used coffee grounds can be processed to form low-cost electrodes. The surface and electrochemical characteristics of microporous activated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
0
5
0
1
Order By: Relevance
“…On the other hand, as regards the experimental value of I = V STE / R Pt defined in Equation as an equivalent current due to ISHE, it was slightly larger at t Pt = 3‐2.5 nm than at 4 nm, but halved at t Pt = 1 nm with the highest V STE . Nowadays, extensive research is conducted on electric double‐layer capacitors as elements supporting a broad voltage range, and the STE conversion elements combined with these capacitors may be used to create electric storage systems. In this case, there is a need to examine the STE element length required to obtain the necessary voltage, as well as ISHE currents required for charge accumulation.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, as regards the experimental value of I = V STE / R Pt defined in Equation as an equivalent current due to ISHE, it was slightly larger at t Pt = 3‐2.5 nm than at 4 nm, but halved at t Pt = 1 nm with the highest V STE . Nowadays, extensive research is conducted on electric double‐layer capacitors as elements supporting a broad voltage range, and the STE conversion elements combined with these capacitors may be used to create electric storage systems. In this case, there is a need to examine the STE element length required to obtain the necessary voltage, as well as ISHE currents required for charge accumulation.…”
Section: Resultsmentioning
confidence: 99%
“…(1867 m 2 g −1 ) and highly porous (1.52 cm 3 g −1 total pore volume) carbon material with a good specific capacitance in organic electrolytes. 47 Yang et al reported later a very high surface area of 2558 m 2 g −1 for CDC produced by KOH activation at 800 °C preceded by carbonization at 600 °C in an inert atmosphere. The study focused on the correlation between the pore size in the carbon material and the dimension of the desolvated ions in the organic electrolyte.…”
Section: Supercapacitorsmentioning
confidence: 99%
“…Sebagian besar karbon aktif komersil yang dibuat dari bahan bakar fosil minyak bumi dan batu bara menjadikannya sangat mahal dan tidak ramah lingkungan, sehingga penelitian beralih pada sumber karbon aktif dari biomass limbah organik yang lebih murah, mudah didapat dan ramah lingkungan (Abioye and Ani, 2015). Berbagai penelitian telah banyak dilakukan dalam penggunaan sumber karbon aktif dari biomass limbah organik sebagai elektroda superkapasitor seperti limbah bubuk kopi (Tashima et al, 2014), daun ketaping (Taer et al, 2018), cangkang kelapa sawit (Misnon et al, 2015), enceng gondok (Zheng et al, 2017), tandan kosong kelapa sawit (Farma et al, 2013), dan cangkang biji karet (Pagketanang et al, 2015). Pada penelitian ini dipilih CBK yang banyak ditemukan di daerah Sumatra barat khususnya daerah ketaping sebagai sumber karbon aktif karena mudah didapat, melimpah, terbarukan dan berkontribusi terhadap pengurangan limbah organik.…”
Section: Pendahuluanunclassified